Ab Initio Calculated Structures and Vibrational Spectra of 1,3-Diethoxy-p-tert-butylcalix[4]crown-5-ether Complexed with Potassium Cation - 최종인 (Bulletin of the Korean Chemical Society, 2007)
Molecular structures were optimized for the 1,3-diethoxycalix[4]crown-5-ether (2) in the various isomers and their potassium-ion complexes by using B3LYP/6-31+G(d,p)//B1LYP/6-31G(d,p) method after ab initio RHF/6-31G calculation. The cone-shaped isomer of 2 with cr-binding mode has shown the strongest binding efficiency among the six different complexes attributed to seven electrostatic interactions between the potassium cation and the oxygen atoms of crown-5-ether and ethoxy groups of the host (2). The vibrational spectra of 2 and its K+-complexes were obtained by restricted Hartree-Fock (RHF) calculations with the 6-31G basis set. The characteristic vibrational frequencies of various C-O-C stretching and bending motions are analyzed. KCI Citation Count: 8